Zastosowanie informatyki w zarządzaniu łańcuchem dostaw w przedsiębiorstwach agrobiznesu - Matouk, Kamal (Application of Computer Science on Supply Chain Management within the Agribusiness Enterprises, 2007)
The main goal of this paper is defining the role of the computer science in the agribusiness enterprises. The paper presents the application of computer science to supply chain management. The modular structure of the SCM system as well as some information technologies applied within this system have been described.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 326-340